Answer:
D
Step-by-step explanation:
The horizontal asymptote is found by considering the ratio of the coefficients of the highest degree terms on the numerator and denominator, that is
coefficient of 6x² on the numerator ⇒ 6
coefficient of 9x³ on the denominator ⇒ 9
The horizontal asymptote is
y =
⇒ y =
→ D
Answer:
1
Step-by-step explanation:
(a+b)(a−b)=a²−b²
tan²(θ)+1=sec²(θ)
(sec(θ)+tan(θ))(sec(θ)−tan(θ))
=sec²(θ)−tan²(θ)
=(tan²(θ)+1)−tan²(θ)
=1
4x-1=-2(x+1)
Distribute
4x-1=-2x-2
Move variable to left and change signs
4x+2x=-2+1
Combine like terms
6x=-1
Divide both sides by 6
X=-1/6
Answer: Decompose means the opposite, to take apart
Step-by-step explanation: In this lesson, the words composition and decomposition are used to describe how irregular figures can be separated into triangles and other polygons. The area of these parts can then be added together to calculate the area of the whole figure.
Answer: =2/5 x
Step-by-step explanation: